1. the equation is y=mx+b. m= slope and b= y-intercept so your answer should be y=2/3x+2
2. point-slope form is y-y1/x-x1=m answer is y+4=-1(x-1)
3. i give up im sorry my brain is fried ;-;
4.uhh i graphed it and attached an image lol
dang i- cant do no more math today lol sorry good luck
Well I am going to assume you need slope-intercept form. So the equation is y=mx+b. m is slope, b is y intercept. So you just plug it in -6= -1/2(6)+b. -6=-3+b. Now you figure out for b so what does b have to be to make the equation equal. Well -3 so -6=-3+-3, or -6=-6.
y=-1/2x-3
Hope that helped
Answer:
h(2)+g(2) = -3
Step-by-step explanation:
Replace the variable (t) with (
2) in the expression.
h (2) = 3 - 5
Replace the variable (t) with (
2) in the expression.
g(2) = 2(2) -5
Replace the function designators in h(2) +g(2) with the actual functions.
h(t) = 3 - 5 +2 (2) ← plug h(2) into 2(t)
Remove parentheses.
3 - 5 + 2(2)
Multiply 2 by 2
3 - 5 + 4 - 5
Subtract 5 from 3
.
-2 + 4 - 5
Add -2 and 4
2 - 5
Subtract 5 from 2
-3
Answer: 14 a hour
Step-by-step explanation:
Answer: -2x + 9
First, Use the distributive property: 3(x+3)-5x (3 multiplied by x is 3x and 3 multiplied by 3 is 9
Next, subtract the variable x: 3x+9-5x (3x-5x=-2x
The answer is -2x+9